Adsorption of Methyl Red Dye on Fixed-Bed Column Using Bottom Ash Adsorbent from Palm Oil Mill Waste - Novi Sylvia; Rozanna Dewi; Fikri Hasfita; Leni Maulinda; Wusnah Wusnah; Azhari Azhari; Zikri Husni Sigian; Balqis Eka Putri; Fitriani Fitriani (Jurnal Kimia Sains dan Aplikasi, 2025)
Methyl red is an azo compound widely applied in the textile industry as a fabric dye. Methyl red is very difficult to decompose because it is stable to light, temperature, and oxidation. One of the simplest and low-cost methods is adsorption. This study aims to determine the characteristics of bottom ash as an adsorbent and analyze the adsorption process with a fixed-bed column system. The research was conducted by varying the flow rate of 5, 10, and 15 L/min, adsorbent bed height of 4, 8, and 12 cm, and contact time of 60, 120, and 180 minutes. The highest removal efficiency, 93%, was achieved at a contact time of 180 minutes, a flow rate of 5 L/min, and a bed height of 12 cm. The physical properties of the bottom ash adsorbent include a pore volume of 0.0032 cm3/g, a specific surface area of 89.801 m2/g, and an average pore size of 58.523 nm. The maximum adsorption capacity was found to be 0.850 mg/g. The adsorption process of methyl red onto bottom ash follows the Langmuir isotherm model.